PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA - Siti Fitriyani Sartika; Ana Setiani; Novi Andri Nurcahyono (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2020)
This study was aims to determine the differences in students mathematical understanding abilities with using snowball throwing learning model compared to direct learning model, and to determine the effect of snowball throwing learning model on improving students' mathematical understanding abilities. The benefit of this study is to provide information about how big the effect of snowball throwing learning model on students' mathematical comprehension abilities. This study used a quasi-experimental method. The Population used in this study was class VIII students of MTs-Al-Musthofa with a total sample 60 people taken by random sampling technique. The instrument that used in this reseacrh is test intrument mathematical comprehension ability consisting of 5 items essays. The results of the study showed that: 1) the ability of students' mathematical understanding using the snowball throwing learning model was better than the direct learning model. 2) There was an increase in the students' mathematical understanding ability using the snowball throwing learning model.